2021
DOI: 10.1016/j.canep.2020.101777
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year study of Retinoblastoma in Uganda: An approach to improving outcome with limited resources

Abstract: Background: Survival of children with cancer in resource-limited regions is very poor compared to better-resourced regions. Retinoblastoma (RB) is a childhood cancer that is commonly reported in many regions of Africa. RB may be safely and effectively treated by non-specialists, which could facilitate more widespread availability of treatment in under-resourced areas.Methods: A ten-year consecutive series of children with RB treated at Ruharo Eye Centre between December 2009 and November 2019 was prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The benefits of building capacity and centralizing care in low-income countries include increasing awareness of the disease and offering ease of access to health care (3,(36)(37)(38). In the low-income countries of Uganda, Senegal, and Nepal, survival rates are 60% (41), 53% (42), and 24% (43), respectively, with metastatic spread reported as the cause of most deaths in all three studies. Survival rates were much higher in developed countries; 99% in the United States (44), 100% in the United Kingdom (45), and 95% in Japan (46); most deaths resulted from trilateral Rb or second malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of building capacity and centralizing care in low-income countries include increasing awareness of the disease and offering ease of access to health care (3,(36)(37)(38). In the low-income countries of Uganda, Senegal, and Nepal, survival rates are 60% (41), 53% (42), and 24% (43), respectively, with metastatic spread reported as the cause of most deaths in all three studies. Survival rates were much higher in developed countries; 99% in the United States (44), 100% in the United Kingdom (45), and 95% in Japan (46); most deaths resulted from trilateral Rb or second malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy has been used worldwide to treat both superficial tumors in the cervix, skin, 61 , 62 and eye, 63 and tumors deeper in the body in the kidney, 64 - 66 liver, 67 , 68 lung, 69 , 70 bone, 71 , 72 prostate, 73 , 74 breast, 75 , 76 and head and neck. 77 In LMICs, cryotherapy has been widely implemented in national programs for prevention and control of cervical cancer throughout Asia and Africa, 78 - 84 particularly after endorsement by the WHO in 2013.…”
Section: Cryotherapymentioning
confidence: 99%
“…In a single-centre study done in the USA (1994–2014), 4 the retinoblastoma survival rate was reported to reach 99% (mean follow-up 4–8 years, depending on age group); in a single-centre study done in the UK (2002–14), 5 it was reported to reach 100% (mean follow-up 5 years); and in a single-centre study done in Japan (1984–2016), 6 it was reported to reach 95% (10-year overall survival), with most deaths occurring from trilateral retinoblastoma in all three studies. In low-income countries, survival rates are significantly lower: 60% (5-year survival) in a single-centre study done in Uganda (2009–19), 7 53% (follow-up time not indicated) in a single-centre study done in Senegal (2006–10), 8 and 24% (10-year survival) in a single-centre study done in Nepal (1998–2008), 9 with the majority of deaths in all three studies occurring from metastatic spread.…”
Section: Introductionmentioning
confidence: 99%